2017
DOI: 10.1111/jtsa.12268
|View full text |Cite
|
Sign up to set email alerts
|

Robust Wilcoxon‐Type Estimation of Change‐Point Location Under Short‐Range Dependence

Abstract: We introduce a robust estimator of the location parameter for the change-point in the mean based on Wilcoxon statistic and establish its consistency for L 1 near-epoch dependent processes. It is shown that the consistency rate depends on the magnitude of the change. A simulation study is performed to evaluate the finite sample properties of the Wilcoxon-type estimator under Gaussianity as well as under heavy-tailed distributions and disturbances by outliers, and to compare it with a CUSUM-type estimator. It sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Notice that a linear process or AR process might not be absolutely regular, but it would be L 1 near epoch dependent; see Example 2.1 in (Gerstenberger, 2018) for linear processes and (Hansen, 1991) for GARCH(1,1) processes. More examples of L 1 NED processes can be found in (Borovkova et al 2001), who also discuss more general L r NED processes, r ≥ 1.…”
Section: Definitions Assumptions and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notice that a linear process or AR process might not be absolutely regular, but it would be L 1 near epoch dependent; see Example 2.1 in (Gerstenberger, 2018) for linear processes and (Hansen, 1991) for GARCH(1,1) processes. More examples of L 1 NED processes can be found in (Borovkova et al 2001), who also discuss more general L r NED processes, r ≥ 1.…”
Section: Definitions Assumptions and Main Resultsmentioning
confidence: 99%
“…An important step of our testing procedure is the estimation of the location k * of the change-point in mean. Gerstenberger (2018) showed that under Assumptions 1 and 2 the Wilcoxon-type change-point location estimator…”
Section: Definition 22 a Stationary Processmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive literature on change point detection and estimation in independent and identically distributed random variables is by Csorgo and Horváth (1997) where mostly a change in mean is considered, or in martingale difference sequences as in Bai (1994) or even change in variance under the assumption that financial returns are independent and identically distributed random variables Inclan and Tiao (1994) which is not a fact when one is working with real financial data. It has over time been done in time series like Chen et al (2005), Ross (2013), Aminikhanghahi and Cook (2017) under different assumptions on dependence, heterogeneity among others Gerstenberger (2018).…”
Section: Introductionmentioning
confidence: 99%